2004
DOI: 10.1108/09534810410538315
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneur‐mentality, gender and the study of women entrepreneurs

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
376
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(398 citation statements)
references
References 28 publications
5
376
0
17
Order By: Relevance
“…In particular, we show that one of the obstacles women face in gaining credibility in traditionally masculine fields is that different standards are used to evaluate men's versus women's performance (Eagly & Karau, 2002). In extending previous discussions that the masculine prescriptive of entrepreneurship causes credibility challenges for women entrepreneurs (Ahl, 2006;Bruni et al, 2004;Gupta, Turban, & Watsi, 2009), we count and categorize how the language and rhetoric used in decision making develops into gender stereotypes that affect financiers' interpretations of potential when entrepreneurs seek financing. While centered on communal and agentic attributes that are universal to men and women (Eagly), we identify aspects of stereotyping that go beyond gender role congruity theory.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In particular, we show that one of the obstacles women face in gaining credibility in traditionally masculine fields is that different standards are used to evaluate men's versus women's performance (Eagly & Karau, 2002). In extending previous discussions that the masculine prescriptive of entrepreneurship causes credibility challenges for women entrepreneurs (Ahl, 2006;Bruni et al, 2004;Gupta, Turban, & Watsi, 2009), we count and categorize how the language and rhetoric used in decision making develops into gender stereotypes that affect financiers' interpretations of potential when entrepreneurs seek financing. While centered on communal and agentic attributes that are universal to men and women (Eagly), we identify aspects of stereotyping that go beyond gender role congruity theory.…”
Section: Introductionmentioning
confidence: 74%
“…Such perceptions develop among venture capitalists when making funding decisions (Johansson & Malmstr€ om, 2013). Regarding private venture capitalists, a stream of research has argued that the gendered rhetoric of social constructions of entrepreneurial potential capture perceptions that likely characterize and differentiate female and male entrepreneurs (Bruni, Gherardi, & Poggio, 2004;Brush, Carter, Greene, Hart, & Gatewood, 2002;Cliff, Langton, & Aldrich, 2005;Smith, 2010). The underlying hypothesis for this reasoning is that gendered characterization effects women's access to finance.…”
Section: Introductionmentioning
confidence: 99%
“…The broader literature on the gender marking of entrepreneurship (Ahl, 2002;Bruni et al, 2004) and gender socialization (Carter et al, 2007;Marlow and Patton, 2005) has demonstrated how gender shapes entrepreneurship, and evidences that women and men are treated differently, albeit often unconsciously. Hence, Brindley (2005, p. 156) argued that women reduce their risks by selecting industries in low-growth sectors of the economy and that this "makes them potentially more vulnerable to exogenous risk sources".…”
Section: Theory and Hypotheses Risk Perceptions Entrepreneurship Andmentioning
confidence: 99%
“…Society at large holds many preconceived ideas about what women and men are expected to do (Bruni et al, 2004;Marlow and McAdam, 2011). The primary purpose of a business is to generate a surplus, a condition that women are just as capable of achieving as men.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…Its mission is to provide the leadership and inspiration to act as a means of expression to the transformation of the role of women in business into a dynamic force (http: The increasing importance of women entrepreneurs has raised an argument that their leadership style is different from their counterpart, male entrepreneurs. In comparing the management styles of women and men entrepreneurs, Bruni, Gherardi and Poggio (2004) explain that women display distinctive features and abilities, "transformational leadership". This type of leadership/management style encourages positive interactions and trustbased relationships with subordinates with whom they also share power and information.…”
Section: Introductionmentioning
confidence: 99%